(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Surveillance system of human rabies in Iran is working with the aim of having no human rabies and 100% access to health services for all the community. Further more, cooperation with veterinary organization and environment protection organization about vaccination of dogs and cats, sampling of suspicious animals and also training the staff and community and attending rabies national committee meetings is performing during the year. Iran has 31 provinces and 386 districts with a different weather condition as Mediterranean weather in the north of Iran and hot and dry weather in the south. As a result the dominant carnivores in the north and North West of Iran are wolves and in other areas of the country it’s fox. However, in the whole country jackals are found frequently and have been considered as the reservoir of rabies in the nature. The health center in villages includes health houses with trained staff and in the next level there are rural health centers with a family physician. In the cities there are health posts in the first level and urban health centers in the next level which have physicians; and also there are hospitals in the districts. The complicated disease are referred from health houses and health posts to rural or urban health centers and in necessary to hospitals. In animal bite and rabies control program educational measures in control and prevention has been provided in all levels. In each district there is facilitated prevention and control center for human rabies in one of the urban or rural health centers or hospitals. More than 700 centers for control and prevention of human rabies are performing in 386 districts with 24-hour staff that had been trained about preventing treatment methods. If the cases of animal bite refer to health houses, health posts or health centers the lesion will be washed with water and soap for 15-20 minutes after registration of the patients and they will be referred to preventing treatment center for human rabies to start vaccination and serum therapy if needed. Further more the patients’ information will be sent to the district health center to be declared to the preventing treatment center for the follow-up. If the cases of animal bite don’t visit the preventing treatment center for rabies they are actively followed-up. In the district health center the information of the patients will be registered in the online portal reporting system. The online information can immediately be seen after registration by the province or national level. In the national level the national guideline for rabies surveillance had been published with cooperation of national rabies committee and they are distributed to all the health centers and preventing treatment centers for rabies in Iran. Considering the national rabies committee decisions two types of vaccines including VERO and PCEC and specific human rabies serum are provided and distributed to all the preventing centers for rabies. Based on the table of information received from preventing treatment centers for rabies, in the year 2011 about 135095 cases of animal bite and 7 cases of rabied had been registered. Based on the national guideline of rabies two types of preventing treatment measures are conducted after animal bite which include 3-dose and 5-dose treatment. The rabies control program in Iran is successfully performing due to 0n time measures.